2007
DOI: 10.2118/07-09-04
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Experimental Technique for Studying Solvent Mass Transfer and Oil-Swelling Effect in the Vapour Extraction (VAPEX) Process

Abstract: In this paper, a new experimental technique is presented to study the solvent mass transfer in heavy oil and the resultant oil-swelling effect by applying dynamic pendant drop volume analysis (DPDVA). In the experiment, a pendant drop of heavy oil is formed inside a visual high-pressure cell, which is initially filled with a solvent (e.g. propane). As the solvent gradually dissolves into heavy oil, the volume of the pendant oil drop keeps increasing due to the oil-swelling effect. The sequential digital images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Once the pendant oil drop is formed, the solvent starts to dissolve into the oil drop. The mass transfer of the solvent into the pendant oil drop continues until the latter is completely saturated with the former 15,16 . In order to examine the effect of mass transfer of the solvent into the heavy oil drop on their interfacial tension, the dynamic interfacial tension is measured in the mass transfer process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the pendant oil drop is formed, the solvent starts to dissolve into the oil drop. The mass transfer of the solvent into the pendant oil drop continues until the latter is completely saturated with the former 15,16 . In order to examine the effect of mass transfer of the solvent into the heavy oil drop on their interfacial tension, the dynamic interfacial tension is measured in the mass transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 also shows that, for the heavy oil-propane system at P=0.90 MPa and T=23.9°C, the variations of the measured dynamic interfacial tensions at the early stage (t<180 s) of the mass transfer process are relatively large (about 9%). These variations may be attributed to the fast and large swelling of the pendant oil drop due to propane dissolution 16 .…”
Section: Resultsmentioning
confidence: 99%
“…The solvent is transferred mainly, via diffusion, to reduce the viscosity of heavy oil in order for gravity forces to overcome capillary forces. Diffusion coefficients can be determined through pressure decay methods, , dynamic pendant drop volume analysis, NMR and X-ray CAT scanning, , and thermal expansion method . Rezaei et al studied the effect of heat transfer on warm VAPEX and found that the condensation of the solvent on the bitumen surface increased the rate of interface advancement, which increased the production of the upgraded oil.…”
Section: Introductionmentioning
confidence: 99%
“…When the immiscible CO 2 is injected into the reservoir, one of the most significant interactions that occur between the gas and the oil is manifested in CO 2 solubility. During solubility, the CO 2 will diffuse into the oil and thus the oil will begin to swell [5][6][7]. Different crude oils will have different solubility based on their composition and properties, such as API gravity and Molecular Weight (MW) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the experiments conducted to evaluate oil swelling depended on transparent visualization experiments that can permit the ability to see the swelling phenomenon. Of these setups, the flow visualization experiments, and the pendant drop methods are the most widely utilized [6,16,17]. Core flooding experiments have also been conducted to study the ability of immiscible CO 2 to increase oil recovery [18].…”
Section: Introductionmentioning
confidence: 99%